PROBLEMS AND PROSPECTS OF USING ECOLOGICAL FINANCIAL AND CREDIT INSTRUMENTS IN THECOUNTRIES OF THE WORLD AND IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The present article deals with maintenance and features of the using of ecological financial and credit instruments which predetermine to the incipience of the ecological economy in the world and in Ukraine.We’ve found its influence to reduction of emissions of greenhouse gases and development of renewable energy sources. It was analyzed socio-economic problems of financing events for the establishment of the "green" economy in the countries of the world. The ways of decision of these problems by using “green” finance and their elements such as climatic finances, climatic positive and negative stimulus, carbon tax, "green" bonds, "green" tariff, "green" certificate etс are offered in this article. We have investigated socio-economic preconditions of receiving financial support from the Green Climate Fund and other international financial organizations to individual Ukrainian enterprises, territorial communities and households in modern terms. We educed the problems of application of "green" tariff in the countries of the world and in Ukraine and explained ways of decision these problems.
Keywords: ecological financial and credit instruments